A 13 cm asymptomatic abdominal aortic aneurysm complicated with arterial obstruction in the left lower limb: A Case report. (October 2021) - Swed, Sarya; Tfankji, Salim; Alkanj, Hussein; Mohamed, Tasneem; Alhalabi, Nawras; Alibrahim, Hidar
Abstract: Abdominal aortic aneurysm is often asymptomatic when it is small to medium in size, up to a maximum of 8 cm, in this case, a patient presented to the vascular surgery department with a complaint of acute pain in the left lower extremity with pallor due to the presence of arterial obstruction. On physical examination, we found a large pulsating mass in the abdomen. After performing a multislice computed tomography, we confirmed the presence of aneurysm with diameters of 13 × 8 cm below the level of the renal arteries. The rarity of this case in the medical literature come from that the aneurysm has reached this size and did not even rupture and did not cause any digestive discomfort or abdominal pain only complicated with an arterial obstruction in the lower left extremity as a result of the dissection that occurred. An emergency surgical operation was performed to remove the aneurysm and install the Dacron joint, and the patient was placed for 24 hours under intensive care and discharged after 5 days to have excellent results with the patient's condition improving without any complications after the operation. In conclusion, aneurysms constitute a serious condition facing vascular surgeons, especially if they are large in size without any symptoms. Highlights: Aortic aneurysms are asymptomatic in most cases. When the aneurysm expands, symptoms such as abdominal pain and back pain may appear. The extreme expansion led to dissociation and arterial obstruction of the left lower limb without typical symptoms.